2021
DOI: 10.3389/fendo.2021.759597
|View full text |Cite
|
Sign up to set email alerts
|

Compelling Evidence Linking CD40 Gene With Graves’ Disease in the Chinese Han Population

Abstract: Mutations in CD40 have been widely reported to be risk factors for Graves’ disease (GD). The gene, along with its cognate ligand CD40L, may regulate pro-inflammatory and immune responses. Rs1883832, located at the -1 position of the Kozak sequence, is the most well-studied single nucleotide polymorphism (SNP) of CD40, and has been confirmed to predispose those with the alteration to GD, regardless of ethnicity. Our genome-wide association study (GWAS) indicated that several SNPs, including rs1883832 located wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Additionally, it impedes HBV DNA replication and facilitates immune recovery subsequent to HBV infection. It is noteworthy that the aforementioned findings primarily pertain to B cells within PBMCs, as opposed to monocytes, thereby aligning with the findings of Jiang et al 26 In their study, Jiang and colleagues demonstrated a marked elevation of CD40 expression in CD19 + B cells compared to CD14 + monocytes. Furthermore, they noted that the CC/CT genotype of rs1883832 exhibited heightened CD40 expression specifically in CD19 + B cells, while such an association was not observed in CD14 + monocytes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Additionally, it impedes HBV DNA replication and facilitates immune recovery subsequent to HBV infection. It is noteworthy that the aforementioned findings primarily pertain to B cells within PBMCs, as opposed to monocytes, thereby aligning with the findings of Jiang et al 26 In their study, Jiang and colleagues demonstrated a marked elevation of CD40 expression in CD19 + B cells compared to CD14 + monocytes. Furthermore, they noted that the CC/CT genotype of rs1883832 exhibited heightened CD40 expression specifically in CD19 + B cells, while such an association was not observed in CD14 + monocytes.…”
Section: Discussionsupporting
confidence: 84%
“…Recent research has identified single-nucleotide polymorphisms (SNPs) in CD40’s Kozak sequence that may affect the start of transcription, and studies have also suggested that SNPs in CD40 are closely linked to autoimmune diseases. 7 , 10 , 11 SNPs in CD40 have the potential to alter CD40’s function, thereby affecting protein expression or activity, and may play a potential role in HBV infection.…”
Section: Introductionmentioning
confidence: 99%